Mechanistic studies of the modulation of cleavage activity of topoisomerase I by DNA adducts of mono- and bi-functional PtII complexes - Malina, Jaroslav; Vrana, Oldrich; Brabec, Viktor (Nucleic acids research, 2009)
Using electrophoresis and replication mapping, we show that the presence of DNA adducts of bifunctional antitumor cisplatin or monodentate [PtCl(dien)]Cl (dien = diethylenetriamine) in the substrate DNA inhibits eukaryotic topoisomerase 1 (top1) action, the adducts of cisplatin being more effective. The presence of camptothecin in the samples of platinated DNA markedly enhances effects of Pt-DNA adducts on top1 activity. Interestingly, the effects of Pt-DNA adducts on the catalytic activity of top1 in the presence of camptothecin differ depending on the sequence context. A multiple metallation of the short nucleotide sequences on the scissile strand, immediately downstream of the cleavage site impedes the cleavage by top1. On the other hand, DNA cleavage by top1 at some cleavage sites which were not platinated in their close proximity is notably enhanced as a consequence of global platination of DNA. We suggest that this enhancement of DNA cleavage by top1 may consist in its inability to bind to other cleavage sites platinated in their close neighborhood; thus, more molecules of top1 may become available for cleavage at the sites where top1 normally cleaves and where platination does not interfere.
Keywords: protinádorové látky; inhibitory enzymů; DNA; štěpení DNA; Antineoplastic Agents; inhibitory topoisomerasy I; Topoisomerase I Inhibitors; DNA Cleavage; DNA-topoisomerasy I; superhelikální DNA; DNA Topoisomerases, Type I; cisplatina; adukty DNA; DNA Adducts; DNA, Superhelical; Enzyme Inhibitors; Cisplatin